Annular Neutrophilic Variant of Pemphigus Foliaceus - Belgaumkar, Vasudha; Shinde, Janhvi; Pradhan, Shekhar; Dange, Kiran; Bhatt, Neelam; Varshney, Sarthak (Dermatology Review/Przegląd Dermatologiczny, 2025)
Pemphigus belongs to autoimmune blistering disorders involving circulating antibodies against desmogleins, the proteins involved in keratinocyte adhesion. Pemphigus foliaceus, one of the pemphigus subtype, is characterised by IgG antibodies against desmoglein 1 present in the granular layer, manifesting as superficial epidermal acantholysis. Various presentations include pemphigus erythematosus and endemic pemphigus foliaceus (fogo selvagem). The annular neutrophilic variant is an uncommon presentation that may mimic other inflammatory or autoimmune conditions, including IgA pemphigus, subcorneal pustular dermatosis, and pustular psoriasis. We report the case of a 63-year-old female diagnosed with annular neutrophilic pemphigus foliaceus, successfully treated with colchicine and rituximab. This case highlights the importance of recognising atypical variants of pemphigus foliaceus and their necessary management.